Development of a new mouse model for coxsackievirus-induced myocarditis by attenuating coxsackievirus B3 virulence in the pancreas. Issue 10 (10th October 2019) - Pinkert, Sandra; Pryshliak, Markian; Pappritz, Kathleen; Knoch, Klaus; Hazini, Ahmet; Dieringer, Babette; Schaar, Katrin; Dong, Fengquan; Hinze, Luisa; Lin, Jie; Lassner, Dirk; Klopfleisch, Robert; et al.
Abstract: Aims: The coxsackievirus B3 (CVB3) mouse myocarditis model is the standard model for investigation of virus-induced myocarditis but the pancreas, rather than the heart, is the most susceptible organ in mouse. The aim of this study was to develop a CVB3 mouse myocarditis model in which animals develop myocarditis while attenuating viral infection of the pancreas and the development of severe pancreatitis. Methods and results: We developed the recombinant CVB3 variant H3N-375TS by inserting target sites (TS) of miR-375, which is specifically expressed in the pancreas, into the 3ʹUTR of the genome of the pancreo- and cardiotropic CVB3 variant H3. In vitro evaluation showed that H3N-375TS was suppressed in pancreatic miR-375-expressing EndoC-βH1 cells >5 log10, whereas its replication was not suppressed in isolated primary embryonic mouse cardiomyocytes. In vivo, intraperitoneal (i.p.) administration of H3N-375TS to NMRI mice did not result in pancreatic or cardiac infection. In contrast, intravenous (i.v.) administration of H3N-375TS to NMRI and Balb/C mice resulted in myocardial infection and acute and chronic myocarditis, whereas the virus was not detected in the pancreas and the pancreatic tissue was not damaged. Acute myocarditis was characterized by myocardial injury, inflammation with mononuclear cells, induction of proinflammatory cytokines, and detection of replicating H3N-375TS in the heart. Mice with chronic myocarditis showed myocardial fibrosis and persistence of H3N-375TS genomic RNA but no replicating virus in the heart. Moreover, H3N-375TS infected mice showed distinctly less suffering compared with mice that developed pancreatitis and myocarditis after i.p. or i.v application of control virus. Conclusion: In this study, we demonstrate that by use of the miR-375-sensitive CVB3 variant H3N-375TS, CVB3 myocarditis can be established without the animals developing severe systemic infection and pancreatitis. As the H3N-375TS myocarditis model depends on pancreas-attenuated H3N-375TS, it can easily be used in different mouse strains and for various applications.